A study for sustainable development in optoelectronics industry using multiple criteria decision making methods - Liu, Chun-Chu; Cheng, An-Chin; Chen, Shih-Hui (Technological and Economic Development of Economy, 2017)
This study assessed the operational efficiency of the optoelectronics industry in the Southern Taiwan Science Park (STSP) between 2007 and 2011 by using multiple criteria decision making methods (data envelopment analysis, Malmquist productivity index and Bootstrap). The data analysis showed that during the study period, meaning that the operational efficiency gap among manufacturers in STSP is widening. Among these manufacturers, eight manufacturers exhibited constant returns to scale, which was more than a half of the overall decision making unit (DMU), indicating that the operational scale of these manufacturers was nearing the optimal scale. Based on Malmquist productivity index (MPI) analysis, the factors that affect the operational efficiencies of optoelectronics manufacturers’ were as follow: operational cost, the number of employees, and the amount of fixed assets. The development should be focused on increasing technological efficiency and technological change in the future. Finally, based on Bootstrap, the results showed that the focus should be on the production technology while improving productive efficiency to ensure sustainable development of the entire domestic optoelectronics industry in the future. First published online: 02 Nov 2015